Coordination polymers based on a glycine-derivative ligand - Vilela, Sergio M. F.
The combination of the glycine-derivative supramolecular salt 4,6-bis(carboxymethylamino)-2-oxo-2,3-dihydro-1,3,5-triazin-1-ium chloride (H(2)bodt center dot HCl) and lanthanide(III) chloride hydrates under hydrothermal conditions (120 degrees C, 48 h) led to the formation of a family of isotypical materials formulated as [Ln(bodt)(Hbodt)] [where Ln(3+) = La3+ (1), (La0.95Eu0.05)(3+) (2) and (La0.95Tb0.05)(3+) (3)]. The synthesis of the novel precursor H(2)bodt center dot HCl is detailed. The structures of H(2)bodt center dot HCl and its intermediate compound were unveiled by single-crystal X-ray diffraction and characterized by standard liquid-state techniques. The crystallographic details of compound 1 were unveiled in the monoclinic P2/c space group by using single-crystal X-ray diffraction, with the crystal structure of 1 comprising a one-dimensional (1)(infinity)[La(bodt)(Hbodt)] coordination polymer. All polymeric materials were fully characterized by FT-IR, electron microscopy (SEM and EDS), powder X-ray diffraction, and elemental and thermogravimetric analyses. The photoluminescent properties of 1 and of the mixed-lanthanide materials 2 and 3 were investigated at ambient and low temperatures. An excited-state intermolecular proton transfer (ESPT) process, induced by intermolecular hydrogen-bonding interactions, is proposed to account for the observed anomalous emission and excitation spectra of 1. Aiming at providing an in-depth understanding of the emission (fluorescence and phosphorescence) properties of the ligand, time-dependent density functional theory (TD-DFT) calculations were also performed.